A Human Anti-M2 Antibody Mediates Antibody-Dependent Cell-Mediated Cytotoxicity (ADCC) and Cytokine Secretion by Resting and Cytokine-Preactivated Natural Killer (NK) Cells. - Venkateswara R Simhadri (PLoS ONE, 2015)
The highly conserved matrix protein 2 (M2) is a good candidate for the development of a broadly protective influenza vaccine that induces long-lasting immunity. In animal models, natural killer (NK) cells have been proposed to play an important role in the protection provided by M2-based vaccines through a mechanism of antibody-dependent cell-mediated cytotoxicity (ADCC). We investigated the ability of the human anti-M2 Ab1-10 monoclonal antibody (mAb) to activate human NK cells. They mediated ADCC against M2-expressing cells in the presence of Ab1-10 mAb. Furthermore, NK cell pro-inflammatory cytokine and chemokine secretion is also enhanced when Ab1-10 mAb is present. We also generated cytokine-preactivated NK cells and showed that they still displayed increased effector functions in the presence of Ab1-10 mAb. Thus, our study has demonstrated that human resting and cytokine-preactivated NK cells may have a very important role in the protection provided by anti-M2 Abs.